Sosialisasi tugas dan tanggung jawab Guru Pendidikan Khusus di SD Inpres Maccini Baru Makassar - Bastiana Bastiana; Tatiana Meidina; Dwiyatmi Sulasminah (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The problem faced by partners was the lack of deepunderstanding of the principal, special education teacher,regular teachers, and parents about the duties andresponsibilities of special education teachers. As a result ofthis lack of knowledge, the special education teaching teacherswere not in accordance with their actual duties andresponsibilities. Therefore, a socialization program was neededin order to enhance the understanding of principals, regularteachers, special education teachers, and parents of childrenwith special needs. The socialization was attended by 39participants. The results of this program showed an increase inunderstanding of the duties and responsibilities of specialeducation teachers at SD Inpres Maccini Baru, Makassar.